Pengembangan Media 3 Dimensi Bina Diri untuk Siswa Tunagrahita - Resita Wulansari (Universitas Negeri Malang, 2016)
Dalam pelaksanaan program bina diri memerlukan banyak ketrampilan dan pemenuhan media pembelajaran yang inovatif dan variatif. Tujuan pengembangan ini adalah menghasilkan sebuah produk pengembangan Media 3 Dimensi (“Busy Book”) bina diri Memakai Sepatu Bertali untuk Siswa Tunagrahita di SMPLB X Kota Malang. Metode penelitian diadaptasi dari model pengembangan research and development dari Borg and Gall. Analisis yang digunakan yaitu penelitian awal (analisis kebutuhan), validasi ahli. Hasil pengembangan secara keseluruhan disimpulkan bahwa pengembangan Media 3 dimensi (“Busy Book”) binadiri Memakai Sepatu Bertali untuk Siswa Tunagrahita sangat layak digunakan.During the implementation of self-development program it requires a lot of skills and fulfillment for innovative and various instructional media which can help learners master their social and practical life at caring for themselves. The purpose of this development is to produce a 3-dimensional media development product («Busy Book») for self-development using lace-up shoes for intellectual disabilities Students at SMPLB X Malang. This development was adapting research and development model put forward by Borg and Gall, method was applied from the initial research (needs of analysis) and expert validation. The overall development results can be deduced that this development is highly eligible for the use of self-development instructions using lace-up shoes for intellectual disabilities students.